Centroamericanidades: Imaginative Reformulation and New Configurations of Central Americanness - Arturo Arias (Studies in 20th & 21st Century Literature, 2013)
The principal question posed in this special issue is: Where is Central America? At a primary level this would appear to be a simple geographical question, even if it were to offer a topology of a qualitatively distinct world…
Keywords: latinidad; Central American identity; Centroamericanidad; imaginary realm; latino/a landscape